STUDI KEGAGALAN SUDU RUNNER TURBIN AIR TYPE FRANCIS (Kasus Penipisan Sudu Runner) - MT, Ir. Edison (Menara Ilmu, 2017)
Hydro turbine runner blades operated for Hydro Power, a failure. This is verydisturbing installation productivity. For that we need more research done on the source offailure in order to do preventive measures and improvements so that the time will come thesame damage does not happen again.This study aims to analyze and find the main causes of failure in the hydro turbinerunner blades . In supported this research is testing the following: Visual Inspection andTesting working fluid water. From the results this study note that the material caracteristicshydro turbine blade runner is G-X5 Cr Ni 134 similar to ASTM A743 with a composition CA6NM content elements as follows: 0.07% C, max 1.5% Mn, 1.0 max % Si, Cr 12,0-13,5%, 3,5-5,0% Ni, 0.70% Mo.The main causes study the hydro turbine runner blades, this water is the thinning theblade wall, the mechanism acidic water as a energy source to encourage high-speed blades torotate the blade, resulting in the collision surface blade, so blade will experience thinning thewalls so the blade runner blade into broken. Runner blade fracture accelerated because of thewater as the driving force and acidic sand.